Effects of N-acetyl-L-cysteine on lifespan, locomotor activity and stress-resistance of 3 Drosophila species with different lifespans. - Shaposhnikov, M.V.; Zemskaya, N.V.; Koval, L.A.; Schegoleva, E.V.; Zhavoronkov, A.; Moskalev, A.A. (Aging, 2018)
N-acetyl-L-cysteine (NAC) is a derivative of the sulphur-containing amino acid L-cysteine with potential anti-aging properties. We studied 3 Drosophila species with contrast longevity differences (D. virilis is longest-lived, D. kikkawai is shortest-lived and D. melanogaster has moderate lifespan) to test the effects of NAC at 8 different concentrations (from 10 nM to 100 mM) on the lifespan, stress-resistance and locomotor activity. Except the adverse effects of highest (10 mM and 100 mM) concentrations NAC demonstrated sexually opposite and male-biased effects on Drosophila lifespan, stress-resistance and locomotor activity and not satisfied the criteria of a geroprotector in terms of the reproducibility of lifespan extending effects in different model organisms. The concentration- and sex-dependent changes in the relative expression levels of the antioxidant genes (Cat/CG6871 and Sod1/CG11793) and genes involved in hydrogen sulfide biosynthesis (Cbs/CG1753, Eip55E/CG5345 and Nfs1/CG12264) suggest the involvement of hormetic mechanisms in the geroprotective effects of NAC.